A secure online examination system - Lim, Jun Kai (Nanyang Technological University, 2022)
An online examination system is a software where a particular institution or organization can conduct and facilitate examinations through an online environment. This software is conducted via the Internet worldwide, Intranet in an environment, or a LAN environment.